A new Punctastriata species (Staurosiraceae, Bacillariophyceae) from a nineteenth century sample collected by Charles-Henri Delogne - van De Vijver, Bart; Wetzel, Carlos E. (Phytotaxa, 2025)
The diatom genus Punctastriata (Staurosiraceae) includes small-celled taxa often indistinguishable from Staurosirella under light microscopy, complicating their identification in ecological and monitoring studies. Examination of a historic sample from Frahan (Belgium, Delogne collection) revealed two distinct Punctastriata species. One, with heteropolar clavate valves and variable spine positioning on both virgae and vimines, is described as Punctastriata davidwilliamsii Van de Vijver & C.E.Wetzel sp. nov. The second corresponds to P. glubokoensis, for which an emended description is provided. Both species were abundant in the Frahan material, and additional observations confirm they are more widespread in Europe than previously recognized. Frequent misidentifications with Staurosirella or poorly defined Punctastriata taxa underline the need for scanning electron microscopy in resolving this genus. The recognition of P. davidwilliamsii refines species concepts within Punctastriata and improves our understanding of the diversity and biogeography of small-celled araphid diatoms in European freshwaters.